Human Rights of Migrants: From Desert Migration to Resettlement - Nnawulezi Uche; Adeuti Bosede Remilekun (Faculty of law Udayana University, 2021)
The issue of desert migration has remained an intractable problem in the context of human rights. Desert migration raises unabated and a major concern because of the problems that come with it. Illegal migration has highlighted the need for and the challenge of having a proper human rights impact assessment of desert migration which will help in providing a suitable legal framework. This article primarily seeks certain protections accorded to migrants on desert migration and identifies problems associated with desert migration and the states of stranded migrants under human rights law. It is written by using a doctrinal legal research methodology that adopts analytical and qualitative approaches and builds its argument on existing literature which is achieved by synthesis of ideas. This article noted that there is a significant protection gap in the international and regional human rights architecture which oftentimes result in inadequate protection of migrants from human rights violation. It is argued that in order to guarantee a robust protection of migrant's rights outside their place of origin, a more integral response to critical human rights and development challenges is capable of addressing the protection gap. Furthermore, the article demonstrated that adopting a new approach with comprehensive instruments on migrant's rights protection and resettlement will be able to eradicate unabated violations of migrant's rights around the globe.